Aural Latency. On the Interaction between Image and Sound in Iconic Notation (Revista Argentina de Musicología, 2019)
Aural Latency. On the Interaction between Image and Sound in Iconic NotationThe implementation of writing as a cultural technique in the field of music enabled the development of different principles of composition and therefore helped to structure acoustic events on a two-dimensional interface (musical score). However, the sound innovations put forward by the avant-garde of the 20th Century challenged the so-called standard notation as optic representation par excellence. Many of the new musical aesthetics exceeded the classical tonal organization calling for new approaches to this medium and giving birth to numerous visualization strategies. Some of these ways of visual projection of sound included iconic (or pictorial) elements that transgressed the syntactic frame of standard music notation. The concept of Aural Latency seeks to shed some light on perceptual aspects of “iconic scores” through the discussion of contemporary writing and image theories that enable a comprehensive understanding of the hybrid nature of this medial phenomenon.
Keywords: graphic music notation; iconic turn; pictorial turn; writing theory